Dynamics and sociability in popular classes families: life’s histories - Bazon, Marina Rezende (Paidéia (Ribeirão Preto), 2000)
This work investigates life's histories of three families that were making part of social programs whose kids were sheltered in a home care center, under protection measure. The goal was to identify and to analyze some inherent aspects of their dynamics and sociability. The data's collected was through institutional reports, interviews with the professional that followed the cases (a social worker) and informal interviews with the three families' members. The results allow affirm that the three families are from a low social status and they started following a nuclear model. In their histories, in front of several material difficulties, we verify the initial group desegregation and the use of survival strategies, including their children institutionalization.